Immune responses to WT1 in patients with AML or MDS after chemotherapy and allogeneic stem cell transplantation. Issue 7 (27th November 2015) - Casalegno‐Garduño, Rosaely; Schmitt, Anita; Spitschak, Alf; Greiner, Jochen; Wang, Lei; Hilgendorf, Inken; Hirt, Carsten; Ho, Anthony D.; Freund, Mathias; Schmitt, Michael
Abstract : Wilms' tumor gene 1 (WT1) is overexpressed in leukemia and WT1‐derived CD8 + T‐cell epitopes for immunotherapies targeting WT1 have been defined. Here, we analyzed expression of WT1 in 226 peripheral blood and bone marrow samples from patients with acute myeloid leukemia or myelodysplastic syndrome (AML/MDS) before and after allogeneic stem cell transplantation (SCT). Transcripts were assessed by quantitative polymerase chain reaction, and WT1‐specific CD8+ cytotoxic T cells (CTL) were monitored by tetramer staining and enzyme‐linked immunospot (ELISPOT) assays. Reduction of WT1 levels correlated with a longer survival ( p < 0.01). Increment of WT1 transcripts eventually resulted in relapse and subsequent death of the patients. In patients with longer survival and continuous complete remission (cCR) after SCT, higher and enduring frequencies of WT1‐specific CTL than in patients developing a relapse were detected. These cells were effector T cells secreting interferon gamma and granzyme B. In summary, WT1 is a suitable marker for the detection of minimal residual disease after SCT or chemotherapy. A rising WT1 signal correlated with a dismal prognosis of the patients. WT1‐specific CD8 + T cells might contribute to the maintenance of a cCR. Targeting WT‐1 by peptide/protein vaccination as well as adoptive transfer of genetically modified T cells are future options in the individualized therapy for AML/MDS patients. Abstract : What's New? Wilms' tumor gene 1 ( WT1 ) is overexpressed in a variety of cancers, including acute myeloid leukemia (AML), where WT1 is a considered to be a promising marker for the assessment of minimal residual disease (MRD). That idea is backed here by data showing that WT1 expression following chemotherapy or allogeneic stem cell transplantation in patients with AML or myelodysplastic syndrome (MDS) correlates with survival. Patients with longer survival times and continuous complete remission also exhibited strong CD8+ T‐cell responses against WT1 gene products. The findings suggest that WT1 is a favorable immunotherapeutic target for AML/MDS.